24 Expanding the provision of palliative medicine education on the graduate entry medicine course at swansea university. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Prosser, Annell; Baker, Idris; Walrond, Hannah
Abstract : Background: The provision of Palliative Medicine education within UK Medical Schools is a subject of ongoing discussion, with wide variation in how much teaching is delivered. With 36% of hospital patients having palliative care needs, all newly qualified doctors require these core skills. At Swansea University, this teaching has previously been scattered throughout the curriculum with little co-ordination. We were given the opportunity to develop a new combined Pain and Palliative Medicine learning week for second year students, aiming to design a structured and balanced week to complement clinical teaching. Methods: Our working group included a third year medical student, who helped to focus our teaching techniques on what would be appropriate for her peers – mature and engaged adult learners with well-developed learning skills. We surveyed previous students to attain their thoughts on existing and future learning opportunities; with responses influential in the development of the week. A similar survey was sent to those who attended the week, to ensure their learning needs were met. Results: There was a 51% absolute increase in those who felt they had sufficient teaching on Palliative Medicine after this week; with a 26% increase in those who felt confident or reasonably confident in their knowledge of Palliative Medicine, and 14% in their communication skills in Palliative Medicine. We will compare with APM data on medical education and consider next steps, including our current work, in using this year's feedback to shape next year's teaching. Conclusions: This exciting opportunity to expand the Palliative Medicine teaching at Swansea University is a further step towards building a workforce better equipped to deliver general palliative care, as well as nurturing and inspiring the next generation of experts. We will present learning from how the week was developed and thinking on how to evolve for the future.